Temporal shifts in safety and efficacy profile of mycophenolate mofetil 2 g versus 3 g daily early after heart transplantation. Issue 9 (18th August 2022) - Braghieri, Lorenzo; Jennings, Douglas L.; Bohn, Bruno; Habal, Marlena; Pinsino, Alberto; Mondellini, Giulio M.; Ladanyi, Annamaria; Latif, Farhana; Clerkin, Kevin; Restaino, Susan; Kurlansky, Paul; Takeda, Koji; et al.
Abstract: Study Objective: Mycophenolate mofetil (MMF) is the gold‐standard immunosuppressive agent in heart transplantation (HT), but dose‐dependent toxicities (e.g., neutropenia) are frequent. Gut bacteria β‐d ‐glucuronidases (GUS) modulate MMF bioavailability, and changes in the intestinal flora may influence the pharmacokinetics of MMF. The objective of this study was to evaluate the safety and efficacy of MMF 1.5 g every 12 h (q12) [high‐dose, HD] versus 1 g q12 [low‐dose, LD] and explore the association between neutropenia and GUS. Measurements: We compared the incidence of acute cellular rejection (ACR) and neutropenia during the first 6 months post‐HT. The association between neutropenia and GUS was investigated in an exploratory analysis on a subset of patients with prospectively collected stool data. Stool samples were analyzed using 16S rRNA sequencing. Main Results: A total of 168 patients (120 MMF‐HD, 48 MMF‐LD; mean age 55.7 years, 79% male) were studied. Neutropenia occurred in 38.6% of patients at a median of 106 [64–143] days. Freedom from neutropenia was lower in MMF‐HD compared with MMF‐LD (57% vs. 73%, p  = 0.03). ACR (≥1R/1B) occurred in 37.5% of patients at a median of 20 [10–96] days, while high‐grade ACR (≥2R/3A) occurred in 11.3% at a median of 14 [9–89] days. Freedom from ACR was similar between groups. MMF‐LD was associated with more high‐grade ACR (hazard ratio [HR] 3.47, 95% confidence interval [CI] 1.09–11.08, p  = 0.03) during the first month, but less neutropenia (HR 0.54, 95% CI 0.29–1.00, p  = 0.05) between 1 and 6 months. GUS‐producing bacteria were more abundant in neutropenic patients. Conclusions: MMF‐LD was associated with higher rates of early high‐grade ACR and lower rates of later neutropenia. Further studies are warranted to test whether temporal MMF dose adjustments and gut microbial composition could improve clinical outcomes post‐HT. Abstract :